Освіта, наука і виробництво у контексті вимог Болонської декларації - Данилишин, М.; Куценко, В. (№3, 2007)
The way of transformation to competitive economics and the role of close interaction of education, science, and employers is substantiated. The attention is focused on improvement of personnel training as a main productive force in the context of Bologna declaration requirements.